Accounting information systems as a critical success factor for increased quality of accounting information - Meiryani; Leny, Susan; Tsundrajat, Jajat; Mat Daud, Zaidi (Peter Lang, 2020)
Accounting information systems within the company add value to the company, such as accurate and timely information so as to perform key activities in value chain effectively and efficiently, improve quality and improve efficiency.The phenomenon that occurs in several organizations in Indonesia shows that the accounting information system has not been qualified so that it has an impact on the lack of quality accounting information. Data testing using SEMPLS. The research method uses explanatory research methods. The results of the study indicate that unqualified accounting information because the lack of accounting information systems. Not yet quality of accounting information is caused by accounting information systems that have not been fully good as expected.